Multi-parametric MR imaging of the anterior fibromuscular stroma and its differentiation from prostate cancer. - Ward, Emily; Baad, Michael; Peng, Yahui; Yousuf, Ambereen; Wang, Shiyang; Antic, Tatjana; Oto, Aytekin (Abdominal Radiology, 2017)
Purpose: To describe MP-MRI features of the normal anterior fibromuscular stroma (AFMS) and identify MR imaging findings that can differentiate it from anterior prostate cancer. Methods: We reviewed MP-MR images and histopathology of patients who underwent pre-operative MRI and prostatectomy between October 2012 and August 2014. Thirty-seven patients with anterior prostate cancer larger than 5 mm and 40 patients with no anterior cancer were included in this study. After correlation with histology and MR images, the size, symmetry, T2, DWI characteristics, and enhancement pattern of normal AFMS and anterior prostate cancer were compared. Results: Normal AFMS was hypointense and symmetric on T2-weighted images (37/40, 93%), whereas anterior prostate cancers, while also hypointense on T2-weighted images, were predominantly asymmetric (6/37, 16%) ( P < 0.001). On high b-value DWI, AFMS was predominantly hypointense (36/40, 90%), whereas anterior prostate cancers were predominantly hyperintense (30/37, 81%) compared to the normal peripheral zone ( P < 0.001). The mean ADC and tenth percentile ADC values of anterior prostate cancers were lower than normal AFMS (7.14 vs. 8.33 (10 mm/s), P < 0.01) and (5.73 vs. 6.95 (10 mm/s), P < 0.01), respectively. On DCE-MR images, AFMS demonstrated a type 1 enhancement curve (35/39, 90%), whereas anterior prostate cancers demonstrated only either a type 3 (23/37, 62%) or type 2 enhancement curve (14/37, 38%) ( P < 0.001). Conclusions: Symmetric T2 appearance, hypointense high b-value DWI signal, relatively higher ADC values, and Type 1 enhancement pattern of the AFMS can be helpful in its differentiation from anterior prostate cancers.